DRIP IRRIGATION OF GARDEN - Kadirov , Z.Z.; Bozorov , B.E.; Avliyokulov, M.M. (Educational Research in Universal Sciences, 2023)
One of the important factors that create soil is relief. The relief shows the formation of soils, the formation of diversity of soil cover. Relief mainly participates in the redistribution of solar radiation and moisture on the earth’s surface. The thickness of alluvial deposits in the regions of Uzbekistan is 1.5-2.0 m. It is known that the appearance of these deposits is connected with human activity, that is, with the development of farming culture for many years. As mentioned above, these deposits are different in many places according to their mechanical composition. Therefore, they are often salted to varying degrees.